Modeling and design control strategy for unwind/rewind system - Ismail, Muhamad Fahezal (2008)
This paper presents the mathematical modeling and designing a control strategy for unwind and rewind system. Unwind and rewind system is widely used in industry that involved the web transportation such as textile, plastic, paper and metal. Basically, the unwind and rewind system consists of three motors which are to control the Unwind, Traction and Rewind. Currently, the system used Programmable Logic Controller (PLC) to control the whole system operation. Strain gauge is used for the system feedback. This project was replaced the PLC to computer controlled method. A new control algorithm that based on the regulator feedback was proposed. The tension observer is introduced as a regulator feedback and dynamic simulation requirement.The mathematical modeling of the system is established base on the tension control, speed control and other elements related to the system. In the control strategy, PID (Propotional Integral and Differential) controller is used to the tension controller and speed controller for simulation and experiment. The xPC-target box is used as a prototype controller to the unwind and rewind tension and speed synchronization. The validation process of the results was performed for both simulation and experimental to see the performance of the system.